Penerapan Sapta Pesona Objek Wisata Benteng Marlborough Kota Bengkulu - Iklil Nadiah Dwiatikah; Yanmesli (Universitas Prof. Dr. Hazairin, S.H, 2024)
This research aims to observe the implementation of Sapta Pesona at the Fort Marlborough tourist attraction, Bengkulu City. The fort has much interesting historical and cultural heritage, and as an important historical site, has great potential to become a tourist attraction. To find out how Sapta Pesona can improve the quality of tourism in the area, researchers used qualitative and descriptive research by collecting information from tourist attraction managers and visitors through observation, interviews and documentation. To attract tourists to return to this tourist spot, there must be elements of Sapta Pesona namely, Safe, Orderly, Clean, Cool, Beautiful, Friendly and Memories. It is hoped that this research can provide suggestions for managers and related parties to improve the quality of tourism in the area. By utilizing the existing historical and cultural potential, Fort Marlborough is expected to become one of the leading tourist destinations in Bengkulu Province, and attract more domestic and foreign tourists.